Antimicrobial peptide-grafted PLGA-PEG nanoparticles to fight bacterial wound infections. (2nd December 2022) - Ramôa, António Miguel; Campos, Filipa; Moreira, Luís; Teixeira, Cátia; Leiro, Victoria; Gomes, Paula; das Neves, José; Martins, M. Cristina L.; Monteiro, Cláudia
Abstract : Production and characterization of AMP (MSI-78 (4–20)) grafted PLGA-PEG NPs by optimization of PLGA-PEG/PLGA-PEG-Maleimide ratios. AMP-NPs are biocompatible and demonstrate improved killing kinetics against S. aureus and P. aeruginosa . Abstract : Wound infection treatment with antimicrobial peptides (AMPs) is still not a reality, due to the loss of activity in vivo . Unlike the conventional strategy of encapsulating AMPs on nanoparticles (NPs) leaving activity dependent on the release profile, this work explores AMP grafting to poly(d, l -lactide- co -glycolide)-polyethylene glycol NPs (PLGA-PEG NPs), whereby AMP exposition, infection targeting and immediate action are promoted. NPs are functionalized with MSI-78(4–20), an equipotent and more selective derivative of MSI-78, grafted through a thiol-maleimide (Mal) Michael addition. NPs with different ratios of PLGA-PEG/PLGA-PEG-Mal are produced and characterized, with 40%PLGA-PEG-Mal presenting the best colloidal properties and higher amounts of AMP grafted as shown by surface charge (+8.6 ± 1.8 mV) and AMP quantification (326 μg mL −1, corresponding to 16.3 μg of AMP per mg of polymer). NPs maintain the activity of the free AMP with a minimal inhibitory concentration (MIC) of 8–16 μg mL −1 against Pseudomonas aeruginosa, and 16–32 μg mL −1 against Staphylococcus aureus . Moreover, AMP grafting accelerates killing kinetics, from 1–2 h to 15 min for P. aeruginosa and from 6–8 h to 0.5–1 h for S. aureus . NP activity in a simulated wound fluid is maintained for S. aureus and decreases slightly for P. aeruginosa . Furthermore, NPs do not demonstrate signs of cytotoxicity at MIC concentrations. Overall, this promising formulation helps unleash the full potential of AMPs for the management of wound infections.